Broad neutralizing antibody response of a monomeric spike–based SARS-CoV-2 bivalent vaccine against diverse variants - Siling Wang; Hui Sun; Yizhen Wang; Zikang Wang; Lunzhi Yuan; Huilin Guo; Jiahua Gao; Miaolin Lan; Yangtao Wu; Huixian Shang; Xiuting Chen; Zheng Chen; et al. (Proceedings of the National Academy of Sciences, 2025)
severeacute respiratory syndrome coronavirus 2 (SARS-CoV-2) bivalent vaccines show potential against variants but lack a full understanding of the immunological mechanisms that drive broadly neutralizing antibodies (bnAbs). This study explored the immunogenicity of a bivalent vaccine in rhesus macaques, containing spike (S) proteins from the prototype (S prototype ) and chimeric S protein (S 1628x ). The vaccine induced bnAbs against multiple variants, including challenging subvariants like EG.1, BA.2.86, and JN.1. The monomeric S protein exposed less accessible regions within the receptor-binding domain (RBD) “inner face” and “NTD face” and subdomains 1, eliciting a diverse array of bnAbs against various Omicron subvariants. Notably, antibodies targeting the conserved RBD inner face, such as 4A5, showed potent neutralization across all tested variants. Structural analyses provide insights into the broad protectiveness of these vaccine-elicited nAbs. This study underscores the potential of bivalent vaccines with monomeric spike proteins to confer broad-spectrum immunity, offering a promising direction for future SARS-CoV-2 universal vaccine design.